A new fluorescent sensor bearing three dansyl fluorophores for highly sensitive and selective detection of mercury(II) ions - Nantanit Wanichacheva (2018)
A novel fluorometric sensor bearing three dansyl moieties based on tris[2-(2-aminoethylthio)ethyl]amine was prepared by a simple approach using a conventional two-step synthesis. The sensor exhibits highly Hg2+-selective ON-OFF fluorescence quenching behavior in aqueous acetonitrile solutions and is shown to discriminate various competing metal ions, particularly Cu2+, Ag+, and Pb2+as well as Ca2+, Cd2+, Co2+, Fe3+, Mn2+, Na+, Ni2+, and Zn2+, with a detection limit of 1.15 × 10-7M or 23 ppb. © 2011 Elsevier Ltd. All rights reserved.